THE INFLUENCE OF PROBLEM HOTS (HIGH ORDER THINKING SKILL) BASED ON DEDUCTIVE HYPOTHESIS ON BASIC PHYSICS 2 TOWARDS STUDENT LEARNING RESULTS - Martin - Martin; Tri Isti Hartini (Jurnal Pendidikan Fisika, 2020)
Research has been conducted on the effect of Giving Hots (High Order Thinking Skill) Based on Deductive Hypothesis on Basic Physics Course 2 on Student Learning Outcomes. The research method uses a mixed method. Where the researchers first developed a product in the form of HOTS questions based on deductive hypotheses in the basic physics course 2, (Research and Development) after the questions were developed and validated, then implemented in learning and assessment (experiment). The validation technique is to ask the expert, in this case as a validator, to check the accuracy and provide an assessment of the appropriateness of the items with the indicators and the editor of the question writing. Based on the results of the validation by the evaluation experts obtained an average percentage assessment of all aspects was 83.33%, the results of the validation by the material experts obtained an average percentage of assessment of the overall aspects was 78.33%. Based on the results of field trials, the average percentage assessment of all aspects was 81.67%. From these results, it shows that the HOTS questions developed are appropriate to be used as an assessment tool in basic physics lectures 2. The influence of HOTS questions based on deductive hypotheses on student learning outcomes can be seen by using the Gain index. In this study, the Gain index value of 0.52, which shows that the effectiveness of giving HOTS questions based on a deductive hypothesis on student learning outcomes in the medium range